Intercropping House of Wonosobo, A Form of Conservative Architectural Locality - Bambang Setyohadi KP; Fisa Savanti; Teguh Prihanto; Isna Pratiwi; Wibowo, Ardiyan Adhi (Universitas Negeri Semarang, 2024)
Highland areas are usually identical to agricultural areas, with abundant produce in the form of vegetables. On the other hand, the community's view of the highland area is considered insufficient in meeting the need for fresh fish, considering its distance from the sea. One of the highlands in Central Java Province that is quite widely known is Wonosobo Regency, where one of the areas has the potential to be a tourist area, namely the Dieng Plateau. If seen from a distance, Wonosobo Regency is quite far from the Java Sea and the Indian Ocean; besides being a highland area, its location is in the middle of Central Java Province. As a highland area, Wonosobo Regency differs from other hilly environments, especially in managing water resources in its residential areas. The management of water resources ultimately fosters a conservative environmental architectural design. The research aims to reveal how the process of forming settlements with wise and regenerative architectural design harmonizes the environment. An exploratory qualitative research method is used to answer the research objectives. The research location is in several neighborhoods in Wonosobo Regency, around the bottom of the Dieng plateau. The results of the study show that the design of residential houses in several residential areas of Wonosobo Regency uses the method of intercropping in the